Parasitic Zoonoses in Humans and Their Dogs from a Rural Community of Tropical Mexico - Antonio Ortega-Pacheco; Juan F. J. Torres-Acosta; Alejandro Alzina-López; Eduardo Gutiérrez-Blanco; Manuel E. Bolio-González; Armando J. Aguilar-Caballero; Roger I. Rodríguez-Vivas; Edwin Gutiérrez-Ruiz; Karla Y. Acosta-Viana; Eugenia Guzmán-Marín; Alberto Rosado-Aguilar; Matilde Jiménez-Coello (Journal of Tropical Medicine)
A cross-sectional study was made on 89 inhabitants and their dogs from a rural community of Yucatan, Mexico, to determine the serological prevalence of some zoonotic parasitic agents. Samples were taken to monitor the presence and intensity of infection with gastrointestinal parasites in dogs. In humans, the serological prevalence of T. canis, T. gondii, and T. spiralis was 29.2%, 91.0%, and 6.7%, respectively. No associations were found between positive cases and studied variables. From the total of blood samples taken from dogs, 87 (97.6%) were seropositive to T. gondii; only 52 viable fecal samples were collected from dogs of which 46.2% had the presence of gastrointestinal parasites with low to moderate intensity; from those, 12% had the presence of T. canis. This study demonstrates the presence of the studied zoonotic agents in the area particularly T. gondii which suggest a common source of infection in dogs and humans and a high number of oocyts present in the environment. Preventive measures must be designed towards good prophylactic practices in domestic and backyard animals (T. canis and T. spiralis). Contaminated sources with T. gondii (food and water) should be further investigated in order to design effective control measures.